To bu(Y) or not to bu(Y): Perceived risk barriers to online shopping among South African generation Y consumers - Christian D. Pentz (Taylor & Francis Group, 2020)
In South Africa the adoption and growth of online shopping is relatively slow. The primary objective of this study was to investigate possible perceived risk barriers that might influence the online shopping behaviour of technologically enabled Generation Y South African consumers. Perceived risk was investigated by means of an online questionnaire in the context of high-involvement products (clothing), and low-involvement products (books). Consideration was also given to experienced and inexperienced online consumers. Results indicate that, for experienced online shoppers, the dimensions of perceived risk that showed significant relationships with their online repurchase intention were psychological risk and social risk (both retailer reputation and social influences), for clothing and books. Time risk was furthermore significant for experienced consumers in terms of books. For inexperienced online shoppers, results showed that financial risk and social risk (retailer reputation), had a significant relationship with online purchase intention for clothing and books. In addition, an equal size multi group analysis between the experienced and inexperienced online consumers for books, indicated no significant differences in the relationship between all the perceived risk dimensions and purchase/repurchase intent. For clothing significant differences were found for the relationships between financial risk and psychological risk and purchase/repurchase intent. The insights gained from the findings can be used by South African online retailers to improve their understanding of technologically enabled consumers and develop more focused and effective marketing strategies to grow online shopping.